GPU pro 7 advanced rendering techniques - Engel, Wolfgang (A K Peters/CRC Press, an imprint of Taylor and Francis, 2016)
The latest edition of this bestselling game development reference offers proven tips and techniques for the real-time rendering of special effects and visualization data that are useful for beginners and seasoned game and graphics programmers alike.
Includes bibliographical references
Keywords: Computer graphics; Digital video; Graphics processing units -- Programming; Real-time data processing; Rendering (Computer graphics); Computer Graphics; Infographie; Vidéo numérique; Processeurs graphiques; Programmation; Temps réel (Informatique); Rendu (Infographie); computer graphics; COMPUTERS / Computer Graphics